A review on advancements in carbon quantum dots and their application in photovoltaics. Issue 8 (8th February 2022) - Kumar, Pawan; Dua, Shweta; Kaur, Ravinder; Kumar, Mahesh; Bhatt, Geeta
Abstract : This review puts forth the in-depth understanding of the fundamentals of carbon quantum dots(CQDs), recent advancements in the field including a thorough discussion on different roles of CQDs to enhance the performance of solar cells and white-LEDs. Abstract : Carbon quantum dots are a new frontier in the field of fluorescent nanomaterials, and they exhibit fascinating properties such as biocompatibility, low toxicity, eco-friendliness, good water solubility and photostability. In addition, the synthesis of these nanoparticles is facile, rapid, and satisfies green chemistry principles. CQDs have easily tunable optical properties and have found applications in bioimaging, nanomedicine, drug delivery, solar cells, light-emitting diodes, photocatalysis, electrocatalysis and other related areas. This article systematically reviews carbon quantum dot structure, their synthesis techniques, recent advancements, the effects of doping and surface engineering on their optical properties, and related photoluminescence models in detail. The challenges associated with these nanomaterials and their prospects are discussed, and special emphasis has been placed on the application of carbon quantum dots in enhancing the performance of photovoltaics and white light-emitting diodes.